2019
DOI: 10.3390/polym11101617
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun 5-chloro-8-hydroxyquinoline-Loaded Cellulose Acetate/Polyethylene Glycol Antifungal Membranes Against Esca

Abstract: Esca is one of the earliest described diseases in grapevines and causes trunk damage and the sudden wilting of the entire plant; it is caused mainly by the species Phaeomoniella chlamydospora (P. chlamydospora) and Phaeoacremonium aleophilum (P. aleophilum). In practice, there are no known curative approaches for fighting esca directly, which is a huge problem for preserving vineyards. Micro- and nanofibrous membranes from cellulose acetate (CA) and cellulose acetate/polyethylene glycol (CA/PEG) containing 5-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…The presence of PVA in the crosslinked fibrous mats, known for its hydrophilicity, is favorable for the release of SQ, SQ.Cu 2+ and SQ.Fe 3+ into the buffer medium. The obtained results are in accordance with the data reported in our previous studies for other fibrous systems containing 8-hydroxyquinoline derivatives [ 36 , 39 , 42 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The presence of PVA in the crosslinked fibrous mats, known for its hydrophilicity, is favorable for the release of SQ, SQ.Cu 2+ and SQ.Fe 3+ into the buffer medium. The obtained results are in accordance with the data reported in our previous studies for other fibrous systems containing 8-hydroxyquinoline derivatives [ 36 , 39 , 42 ].…”
Section: Resultssupporting
confidence: 93%
“…Recently, aromatic heterocyclic compounds from the group of 8-hydroxyquinoline, which have useful properties—antibacterial, antifungal, antitumor, antioxidant, anti-inflammatory and antiviral—and are characterized by low toxicity [ 31 , 32 , 33 , 34 ], have been studied intensively. Previously, we have reported on the incorporation of 8-hydroxyquinoline derivatives into electrospun materials from synthetic polymers [ 35 , 36 , 37 ], chitosan and its derivatives [ 19 , 38 ] and other natural polymers [ 39 , 40 ]. We have also reported the chemical immobilization of 5-amino-8-hydroxyquinoline onto the surface of electrospun fibers from styrene/maleic anhydride copolymers [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal conditions for the successful preparation of fibrous materials from cellulose acetate (CA) and cellulose acetate/polyethylene glycol (CA,PEG) containing 5-chloro-8-hydroxyquinolinol (5-Cl8Q) were previously found [ 18 ]. The following fibrous mats were prepared by electrospinning: CA, CA/5-Cl8Q, CA,PEG, and CA,PEG/5-Cl8Q.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, it was shown that 8Q derivatives: potassium 5-nitro-8-hydroxyquinolate (K5N8Q) and 5-chloro-8-hydroxyquinolinol (5-Cl8Q), can be successfully incorporated into fibers from poly(lactic acid), poly(butylene succinate), cellulose acetate [ 17 , 18 ], poly(vinylidene fluoride), and poly(vinylidenefluoride- co -hexafluoropropylene) [ 19 ] in order to impart antibacterial and antifungal activities of the obtained fibrous materials. Up until now, no literature data are available on the incorporation of 5-Cl8Q in electrospun materials for local cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of low molecular weight derivatives of 8-hydroxyquinoline into fibrous polymer materials obtained by electrospinning is of interest because it allows combining the valuable biological properties of 8-hydroxyquinoline derivatives with the advantages of electrospun materials. In our previous study, we obtained fibrous membranes on the basis on cellulose acetate loaded with an antifungal agent for active protection against spore penetration and plant infection in vineyards [25]. However, the incorporation of low molecular weight derivatives significantly lower the physicochemical properties and therefore they need to be improved.…”
Section: Introductionmentioning
confidence: 99%